Wound Healing as Well as Fibroblasts and Neutrophil Numbers in a Skin Exposed to Infrared and Electrical Stimulation - Shaheen E. Jaafar (Kirkuk Journal of Science, 2011)
Objective: To investigate wound healing as well as fibroblasts and neutrophil numbers on a limited skin field which is previously exposed to combined Infrared and Electrical stimulation. Methods: 20 male rabbits were randomly assigned to two groups each one of 10 animals. The experimental group was exposed to combine Infrared (IR) and Electrical Stimulation (ES) at dorsal area for three days respectively, in day four an incision was made in the center of exposed skin then sutured. A biopsies were taken at 24,48,72 hours, week and two weeks after surgery for counting of fibroblasts and neutrophil numbers as well as for histological observation. The same procedure was made for control group without exposing to radiation and stimulation. Results: There was statistically significant difference in fibroblasts and neutrophil numbers between two groups (p